2021
DOI: 10.1186/s12941-021-00464-5
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infections caused by Klebsiella pneumoniae and Serratia marcescens isolates co-harboring NDM-1 and KPC-2

Abstract: Carbapenem-resistant Enterobacteriaceae are a worldwide health problem and isolates carrying both blaKPC-2 and blaNDM-1 are unusual. Here we describe the microbiological and clinical characteristics of five cases of bloodstream infections (BSI) caused by carbapenem-resistant Klebsiella pneumoniae and Serratia marcescens having both blaKPC-2 and blaNDM-1. Of the five blood samples, three are from hematopoietic stem cell transplantation patients, one from a renal transplant patient, and one from a surgical patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…In recent years, several studies have reported the emergence of pathogens coproducing multiple carbapenemases. In this regard, while coproduction of OXA-48 and NDM-1 has been previously reported ( 46 , 47 ), coproduction of KPC-2 and NDM-1 among K. pneumoniae isolates increased during the COVID-19 pandemic as a major challenge for clinical laboratories ( 3 , 4 , 19 , 43 45 ). CZA has demonstrated both excellent in vitro and in vivo activities against class A carbapenemase producers.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In recent years, several studies have reported the emergence of pathogens coproducing multiple carbapenemases. In this regard, while coproduction of OXA-48 and NDM-1 has been previously reported ( 46 , 47 ), coproduction of KPC-2 and NDM-1 among K. pneumoniae isolates increased during the COVID-19 pandemic as a major challenge for clinical laboratories ( 3 , 4 , 19 , 43 45 ). CZA has demonstrated both excellent in vitro and in vivo activities against class A carbapenemase producers.…”
Section: Discussionmentioning
confidence: 74%
“… a MICs were determined by broth microdilution method according to CLSL and EUCAST guidelines ( 18 , 19 ). The MIC reduction of ATM (aztreonam), CAZ (ceftazidime), and CZA (ceftazidime-avibactam) was evaluated in the presence of avibactam (AVI; 4 µg/mL), dipicolinic acid (DPA; 500 µg/mL), and EDTA (320 µg/mL).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though this organism exhibits a wide range of virulence factors and is relatively weak in virulence, it can infect critically ill or immunocompromised patients, as well as infants and newborns [ 4 , 5 , 6 ]. Researchers have pointed out that this microorganism could cause multiple infections, including meningitis, pneumonia, septicemia, and urinary tract infections, associated with poor clinical outcomes [ 7 , 8 , 9 , 10 ]. Due to their capability of adherence to invasive hospital equipment and forming biofilm, nosocomial infections caused by S. marcescens were difficult to treat [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Анализ нуклеотидных последовательностей паттернов устойчивости позволил установить, что присутствие bla NDM с высокой частотой ассоциировано с наличием в геноме микроорганизма детерминант устойчивости к другим антибактериальным ЛС (AmpC, другие типы карбапенемаз -OXA-48, VIM и KPC), что значительно сужает спектр ЛС для лечения пациентов, инфицированных микроорганизмами -продуцентами NDM-1. Как правило, NDM-продуцирующие микроорганизмы устойчивы к действию всех групп антибактериальных ЛС и чувствительны лишь к полимиксинам (колистину) и тигециклину [31,[47][48][49][50].…”
unclassified